2021
DOI: 10.1101/2021.05.30.21257971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterologous ChAdOx1 nCoV-19 and BNT162b2 prime-boost vaccination elicits potent neutralizing antibody responses and T cell reactivity

Abstract: Background Heterologous prime-boost schedules with vector- and mRNA-based COVID-19 vaccines are already administered, but immunological responses and elicited protection have not been reported. Methods We here analyzed a cohort of 26 individuals aged 25-46 (median 30.5) years that received a ChAdOx1 nCoV-2019 prime followed by a BNT162b2 boost after an 8-week interval for reactogenicity, antibody responses and T cell reactivity. Results Self-reported solicited symptoms after ChAdOx1 nCoV-2019 prime were in l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 40 publications
7
52
0
Order By: Relevance
“…The data presented by us on the humoral immune response after heterologous SARS-CoV-2 vaccination are consistent with the few available clinical studies [16,18,17,19]. A recent preprint reports significant higher anti-S-antibody titres in a group of 26 individuals who first received an AZD1222 vaccination followed by re-vaccination with BNT162b2 compared to 14 individuals that were vaccinated twice with BNT162b2.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The data presented by us on the humoral immune response after heterologous SARS-CoV-2 vaccination are consistent with the few available clinical studies [16,18,17,19]. A recent preprint reports significant higher anti-S-antibody titres in a group of 26 individuals who first received an AZD1222 vaccination followed by re-vaccination with BNT162b2 compared to 14 individuals that were vaccinated twice with BNT162b2.…”
Section: Discussionsupporting
confidence: 85%
“…In the first quarter of this year, however, only a few animal experimental data were available on the immunological outcome of the proposed heterologous vaccination scheme [13, 14]. Several studies have now appeared on the immunogenicity of the heterologous vaccination scheme in humans [16, 21, 17-20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a preliminary study on 830 subjects, in whom the adverse effects (AEs) were analyzed following either two doses of the same vaccine, Pfizer or AstraZeneca, or two doses of different vaccine types, the first Pfizer and the second AstraZeneca, or vice versa, showed a higher prevalence of AEs in the group receiving different vaccine types than the group receiving the same type [43]. The higher prevalence of AEs in patients receiving heterologous vaccine doses was not confirmed in two smaller studies, the first on 326 healthcare workers [44] and the other on 26 subjects [45]. In the latter study, cellular and humoral immunogenicity were explored and the results confirmed the data on the high stimulation of the immune system by the heterologous immunization already observed in the Spanish study, even towards the variants of concern.…”
Section: Covid-19 Vaccinesmentioning
confidence: 86%
“…Another limitation is the lack of assaying neutralizing SARS-CoV-2 specific antibodies. However, previous studies have already demonstrated that total spike-binding Ig titers strongly correlate with the amounts of neutralizing antibodies and are therefore a suitable measure for humoral protection from SARS-CoV-2 infection 5,[40][41][42] . In summary, we consider the description of disparate vaccine effects on the immediate immune response the strength of our study and we believe that our results will be of use for further optimization of vaccination strategies.…”
Section: Figure Discussionmentioning
confidence: 99%